2019
DOI: 10.1108/ci-08-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of innovation in a contractor company

Abstract: Purpose In the construction industry, it has proven difficult to implement and realize innovation efforts, for example in the development of industrialized construction and use of platform concepts. Thus, the purpose of this study is to characterize the innovation diffusion process in the social system of a large Swedish contractor company. Specifically, the diffusion of three innovative industrialized house-building (IHB) platforms and factors affecting their adoption and implementation (particularly effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The initiation and implementation of platforms can be described as 'diffusion' (Lundberg et al, 2019). How this takes place is dependent on the characteristics of the industry, and multiple social networks acting across multiple dimensions such as firm size and time (Shibeika A and Harty C , 2015 ;Rogers, 2005, Rogers 1995)…”
Section: Platform Design Dilemmasmentioning
confidence: 99%
See 1 more Smart Citation
“…The initiation and implementation of platforms can be described as 'diffusion' (Lundberg et al, 2019). How this takes place is dependent on the characteristics of the industry, and multiple social networks acting across multiple dimensions such as firm size and time (Shibeika A and Harty C , 2015 ;Rogers, 2005, Rogers 1995)…”
Section: Platform Design Dilemmasmentioning
confidence: 99%
“…Sexton et al (2006) observed digital adaption by SME's was focused on short strategic horizons (months). Whereas Lundberg et al (2019) found the adoption of product platforms at the level of the construction firm were yet to be fully implemented throughout the social system after 10 years.…”
Section: Diffusion Of Platform Thinking As An Innovation In the Suppl...mentioning
confidence: 99%